Phytochemical investigation, anti-inflammatory, antipyretic and antinociceptive activities of Zanthoxylum armatum DC extracts-in vivo and in vitro experiments. Issue 11 (November 2020) - Alam, Fiaz; Din, Kinza Mohammad; Rasheed, Rukhba; Sadiq, Abdul; Jan, Muhammad Saeed; Minhas, Amber Mehmood; Khan, Arifullah
Abstract: Zanthoxylum armatum (ZA) a commonly used medicinal plant was investigated for phytochemical, anti-nociceptive, anti-inflammatory and antipyretic effects. Extract and total alkaloids from fruit and leaves significantly (p < 0.001) reduced the rectal temperature in mice. The effects of bark and root extracts were less significant. In writhing and tail flick methods both the extract and total alkaloids from fruit showed significant (p < 0.05 and p < 0.001) antinociceptive activity. The fruit extract and crude alkaloids showed significant (p < 0.01) lowering of inflammation of paw edema in mice. Crude alkaloids from fruit and leaves showed significant enzyme inhibition with lower IC50 values for 15 and 69 against COX and 21 and 62 μg/ml against LOX. This study rationalize the usage of this spice in traditional medicine for management of pain and inflammation involving LOX and COX inhibition as possible mechanism. GC-MS analysis revealed the presence of various constituents which might contributed towards the pain and inflammation alleviation. Abstract : Zanthoxylum armatum ; Fruits and leaves; anti-inflammatory; antinociceptive; COX; LOX; GC-MS analysis; Chemistry; Organic chemistry; Biological Sciences; Pharmaceutical Science; Health Sciences; Pharmacology; Alternative Medicine